The Values of the Virtual. Issue 2 (6th October 2022) - Ali, Rami
ABSTRACT: How do we assign values to virtual items, which include virtual objects, properties, events, subjects, worlds, environments, and experiences? In this article, I offer a framework for answering this question. After considering different value theses in the literature, I argue that whether we think these theses mutually exclusive or not turns on our view about the number of value‐salient kinds virtual items belong to. Virtual monism is the view that virtual Xs belong to only one value‐salient kind in relation to X. Virtual pluralism is the view that they belong to more than one value‐salient kind. I argue for two claims. First, virtual monism is mistaken. Minimally some virtual Xs are Xs, while others are not. Second, dualistic virtual pluralism is also mistaken because it is too coarse grained. Instead, I argue for fourfold pluralism: virtual items either represent an original's properties or reproduce essential properties and do so to lesser or greater extents. This gives us four value‐salient kinds of virtual X: virtual reproductions, simulations, representations, and simulacra of X. I apply this view to various debates in the literature and conclude with a discussion of less basic hybrid kinds.